2005
DOI: 10.1161/01.atv.0000151987.04607.24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training and Deconditioning on Platelet Aggregation Induced by Alternating Shear Stress in Men

Abstract: Objective-Alternating shear stress, which resembles the flow condition in stenotic arteries, induces platelet aggregation.This study investigated how exercise training and deconditioning influence alternating shear-induced platelet aggregation (ASIPA) and clarify the mechanisms underlying ASIPA. Methods and Results-Thirty healthy male sedentary subjects were randomly divided into control and trained groups. The trained men were trained on a bicycle ergometer at Ϸ60% of maximal oxygen consumption for 30 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 47 publications
4
61
0
2
Order By: Relevance
“…37 The differences between these findings and those of our study could be explained by the intensity and duration of exercise; although intense and acute exercise could have unfavorable effects on vWF, both moderate and chronic resistance and aerobic exercise seem to have a favorable impact on endothelial function. This hypothesis is supported by the results of a study by Wang et al 38 showing, in 30 sedentary subjects, that short-term strenuous exercise increased vWF factor levels in both the control and trained groups, whereas at rest and immediately after exercise, vWF binding was reduced by training. In this trial, deconditioning reversed the effects of training on resting and postexercise state, mirroring the results of our study, in which all the beneficial effects on endothelial function were lost after 1 month of detraining.…”
Section: Discussionsupporting
confidence: 53%
“…37 The differences between these findings and those of our study could be explained by the intensity and duration of exercise; although intense and acute exercise could have unfavorable effects on vWF, both moderate and chronic resistance and aerobic exercise seem to have a favorable impact on endothelial function. This hypothesis is supported by the results of a study by Wang et al 38 showing, in 30 sedentary subjects, that short-term strenuous exercise increased vWF factor levels in both the control and trained groups, whereas at rest and immediately after exercise, vWF binding was reduced by training. In this trial, deconditioning reversed the effects of training on resting and postexercise state, mirroring the results of our study, in which all the beneficial effects on endothelial function were lost after 1 month of detraining.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, exerciseinduced increases in blood pressure and blood flow may enhance platelet activation due to increased shear stress. 4 Several studies using single parameters have shown that strenuous exercise enhances both blood coagulation and fibrinolysis. 6,7 Exercise increases thrombin generation, 6 and plasma F1ϩ2 levels were indeed elevated in the present study.…”
Section: Et Al Thrombin Inhibition During Stress 411mentioning
confidence: 99%
“…2,3,4 Thus, exercise increases circulating activated platelets, platelet-platelet and platelet-leukocyte aggregates, as well as the CD11b expression of circulating leukocytes and leukocyte secretion (elastase) in vivo. 3 Exercise also enhances the responsiveness of platelets and leukocytes to agonist stimulation in vitro.…”
mentioning
confidence: 99%
“…An animal study showed that exercise training reduced the tendency toward thrombosis induced by laser injury to blood vessels [48]. Some studies have identified that a moderateintensity exercise training (60% VO 2max for 30 min per day, 5 days/week for 8 weeks) reduced resting and strenuous exercise-induced platelet aggregation and platelet adhesion under shear flow in men [19], and in women in a mid-follicular menstrual phase [23], which were accompanied by decreased vWF binding to platelets and expression of P-selectin on platelets [49]. Several mechanisms potentially explain why exercise training reduced the extent of shear-induced platelet activation.…”
Section: Effects Of Exercise Training and Physical Deconditioningmentioning
confidence: 99%